PENGARUH PENGGUNAAN BALANCE SCORECARD TERHADAP KINERJA USAHA MIKRO DI SURABAYA - Albertus Daru Dewantoro (Jurnal Kewirausahaan dan Bisnis, 2021)
The Balanced Scorecard (BSC) managerial practice is generally used by large companies. As the education level of micro business actors increases, the implementation of BSC in micro business management is increasing. BSC to help businesses in the face two fundamental problems, which measures the performance of the organization effectively and implement strategies to improve performance. This study explores the effect of using the BSC on the performance of micro-enterprises, as well as knowing the relationship between firm size and the ability to implement the BSC in micro-enterprises through descriptive statistical approaches and linear regression analysis. The study was conducted on micro-enterprises in Surabaya with the category of having assets or net worth of up to IDR 50 million (not including land or building for business premises) and annual sales turnover of up to IDR 300 million. Total respondents in this study is as much as 153 respondents. The study confirmed that the size of the company has an influence on the readiness of the implementation of the BSC, these results are consistent with research Kimberly & Evanisko, (1981); Nord & Tucker, (1987); Hoque, (2000) and Sherma (2020). This research also shows that the greater the level of BSC implementation of a business, the higher the performance of business achieved in line with the findings by Hoque, (2000); Ondieki, (2017); Dhaifallah,  (2018). Company size affects the readiness of micro-enterprises in implementing the BSC. BSC managerial practices proven to improve the performance of micro-enterprises. BSC practice requires readiness with the support of increasing company size; micro businesses should involve labor in the operations. With an adequate company size, the BSC implementation practice can run optimally and have an impact on achieving better business performance.Keywords: BSC, Business Performance, Firm Size, Micro Enterprise